2020
DOI: 10.1063/5.0014658
|View full text |Cite
|
Sign up to set email alerts
|

Laser cooling in a chip-scale platform

Abstract: Chip-scale atomic devices built around micro-fabricated alkali vapor cells are at the forefront of compact metrology and atomic sensors. We demonstrate a micro-fabricated vapor cell that is actively-pumped to ultra-high-vacuum (UHV) to achieve laser cooling. A grating magneto-optical trap (GMOT) is incorporated with the 4 mm-thick Si/glass vacuum cell to demonstrate the feasibility of a fully-miniaturized laser cooling platform. A two-step optical excitation process in rubidium is used to overcome surface-scat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…The approach is generalizable to a wide range of experimental components and will transform applications as diverse as miniaturized optical devices, vacuum systems and magnetic field generation. Our work complements previous studies of integrated laser sources [20][21][22] and miniaturized vacuum chambers [23] and expands preliminary studies of the utility of additive manufacturing in the setting of quantum technologies [24,25]. Specifically, we demonstrate a new approach to experimental design in free-space optics, where the overwhelming majority of the adjustable components are eliminated and most of the optical elements are mounted in a monolithic, ad-ditively manufactured mount within pre-aligned push-fit slots.…”
Section: Introductionsupporting
confidence: 64%
“…The approach is generalizable to a wide range of experimental components and will transform applications as diverse as miniaturized optical devices, vacuum systems and magnetic field generation. Our work complements previous studies of integrated laser sources [20][21][22] and miniaturized vacuum chambers [23] and expands preliminary studies of the utility of additive manufacturing in the setting of quantum technologies [24,25]. Specifically, we demonstrate a new approach to experimental design in free-space optics, where the overwhelming majority of the adjustable components are eliminated and most of the optical elements are mounted in a monolithic, ad-ditively manufactured mount within pre-aligned push-fit slots.…”
Section: Introductionsupporting
confidence: 64%
“…Magnetic coils optimised for low power consumption can be designed and fabricated 18 , and the optics for laser cooling can be simplified to a single beam illuminating a pyramidal or planar optic [19][20][21] . However, while key progress has been made in developing miniaturised vacuum systems for 'hot' ions 22,23 and laser-cooled atoms [24][25][26][27][28] , a chamber should ideally be devoid of any challenging bulky components or appendages, with integrated pump and atom source, enabling suitable vacuum in an apparatus with a truly compact form factor.…”
mentioning
confidence: 99%
“…Compared to the atomic fluorescence, the light scattered in the cell can be high, due to diffracted light from the grating hitting the cell walls. A clean signal from the atoms is detected by a photodiode in a spatial filtering lens system 27 , minimising light not originating from the atom trapping point (Fig. 1 (a)).…”
mentioning
confidence: 99%
“…Recent work has demonstrated a dramatic reduction of the cooling platform to the chip-scale by combining an anodically bonded glass-silicon-glass vapour cell with a diffractive optical element that redirects a single incident beam into the components required for laser cooling 19 . However, such systems have demonstrated that the detection of cold atoms is made difficult by the reduced optical access of the cell and light scattering from the grating and cell surfaces.…”
mentioning
confidence: 99%
“…However, such systems have demonstrated that the detection of cold atoms is made difficult by the reduced optical access of the cell and light scattering from the grating and cell surfaces. As such, the authors required adopting a non-trivial two-photon spectroscopy scheme for improved detection, greatly increasing both the size and complexity of the optical system 19,20 .…”
mentioning
confidence: 99%